2013
DOI: 10.1021/jz402352d
|View full text |Cite
|
Sign up to set email alerts
|

Design and Applications of Noncanonical DNA Base Pairs

Abstract: While the Watson-Crick base pairs are known to stabilize the DNA double helix and play a vital role in storage/replication of genetic information, their replacement with non-Watson-Crick base pairs has recently been shown to have interesting practical applications. Nowadays, theoretical calculations are routinely performed on very complex systems to gain a better understanding of how molecules interact with each other. We not only bring together some of the basic concepts of how mispaired or unnatural nucleoba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
41
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 91 publications
1
41
0
Order By: Relevance
“…3d), to which corresponds the torsion vibration of the NH 2 group of the G base with imaginary frequency ν і =-178.2i cm -1 . This fast (τ 99.9% =6.09·10 -8 s) (Table S2) and large amplitude quantum oscillation of the G·T(w 2 ) base mispair allows it to be incorporated into the structure of the DNA double helix, since its energy is significantly less than the energy of the stacking interactions of the neighbouring Watson-Crick DNA base pairs [80]. 11 The third novel G*·Т(WC)↔G·Т(w 2 ) pathway (Table 5 and Figs.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…3d), to which corresponds the torsion vibration of the NH 2 group of the G base with imaginary frequency ν і =-178.2i cm -1 . This fast (τ 99.9% =6.09·10 -8 s) (Table S2) and large amplitude quantum oscillation of the G·T(w 2 ) base mispair allows it to be incorporated into the structure of the DNA double helix, since its energy is significantly less than the energy of the stacking interactions of the neighbouring Watson-Crick DNA base pairs [80]. 11 The third novel G*·Т(WC)↔G·Т(w 2 ) pathway (Table 5 and Figs.…”
Section: Methodsmentioning
confidence: 99%
“…It is logical to suggest that the barrier of the G·Т(w)→G*·Т(WC) mutagenic tautomerisation of the wobble G·Т(w) base mispair in the recognition pocket of the DNA-polymerase reduces comparably with the isolated state, in particular, due to the stacking interactions [80]. Table 2) is much greater than the energy of the bases hydration by the corresponding sites of the interaction [85][86][87].…”
Section: Methodsmentioning
confidence: 99%
“…The experimental proof further substantiates the conceivability of an A-C mispair based pH switch. In addition, it has been observed that pHdependent molecular switches can be constructed harnessing the stability of a protonated A-C mispair (Jissy & Datta, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…3 ZnO nanoparticles have unique physical and chemical properties and potential biomedical applications by virtue of their nontoxic nature, low cost, biosafety, biocompatibility and wide usage in daily life such as drug carriers, cosmetics, etc. [16][17][18][19][20] Nano ZnO prefers to bind with a ring nitrogen atom (N-site) relative to other binding sites of the DNA bases; the adsorption strength of ZnO with the N-site of guanine is much higher than that with other sites. 11 The photoactive surfaces of the nanoparticles produce reactive oxygen species that can potentially cause oxidative stress which leads to cellular protein, lipid and DNA damage.…”
Section: Introductionmentioning
confidence: 99%